2016
DOI: 10.23953/cloud.ijavst.170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Ovulation Synchronization Protocols on Estrus Response, Conception Rate and Blood Biochemical Profile in Anoestrus Buffaloes

Abstract: This study evaluated the fertility response and plasma profile of biochemical and mineral constituents in 46 postpartum anoestrus (>90 days) buffaloes treated under field conditions with TriU-B/PRID, Ovsynch and Heatsynch protocols (n=12 each), keeping untreated anoestrus control (n=10) and normal cyclic control (n=10) groups. The estrus induction response with 3 treatment protocols was 83.33, 83.33 and 91.66 % respectively within 2-3 days of PGF 2 α injection. The conception rates (CRs) obtained at induced es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 2 publications
8
2
1
Order By: Relevance
“…In Heatsynch protocol total 90 per cent (9/10) buffalo heifer showed estrus symptoms at the time of insemination. Similar result was recorded by Buhecha et al [16] in anestrues buffaloes.…”
Section: Intensity and Induction Of Estrussupporting
confidence: 91%
See 2 more Smart Citations
“…In Heatsynch protocol total 90 per cent (9/10) buffalo heifer showed estrus symptoms at the time of insemination. Similar result was recorded by Buhecha et al [16] in anestrues buffaloes.…”
Section: Intensity and Induction Of Estrussupporting
confidence: 91%
“…However, 100 per cent estrus was recorded following heatsynch protocol in buffalo by Ali et al [17] and Mohan et al [18] In Ovsynch protocol total 80 per cent (8/10) buffalo heifers showed estrus induction at the time of insemination. Similar result was recorded by Jabeen et al [19] Thorat et al [20] , Savalia et al [21] and Buhecha et al [16] in anoestrus buffaloes. In Doublesynch protocol total 80 per cent (8/10) buffalo heifer showed estrus symptoms at the time of insemination.…”
Section: Intensity and Induction Of Estrussupporting
confidence: 90%
See 1 more Smart Citation
“…In Heatsynch protocol total of 90 percent (9/10) of buffalo heifers showed estrus symptoms at the time of insemination. A similar result was recorded by Buhecha et al [13] in anestrues buffaloes. However, 100 percent estrus was recorded following heatsynch protocol in buffalo by Ali et al [14] In Doublesynch protocol total of 80 percent (8/10) of buffalo heifer showed estrus symptoms at the time of insemination.…”
Section: Group-iisupporting
confidence: 90%
“…2. [13] in anestrous buffaloes and a lower conception rate (10.00%) in buffaloes Yotov et al, [11] was observed.…”
Section: Fertility Responsementioning
confidence: 90%